Implementasi QR Code untuk Sistem Penyewaan Lapangan Futsal Berbasis Android - Mahardika, Fajar; Sumantri, Raden Bagus Bambang; Ripai, Rizki; Pari, Riki Aldi (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2024)
This research aims to implement QR code technology in an Android-based futsal field rental system. The development method used is an Android-based software development method (Mobile Apps Development). QR codes are used as a medium for user identification and verification when ordering a futsal field. This system is designed to make it easier for users to make field reservations quickly and efficiently. Users can make orders via the Android application by scanning the QR code available at the futsal field location. The implementation results show that using QR codes can speed up the reservation process and reduce the possibility of data input errors. Apart from that, using this system can also improve the user experience in ordering futsal fields. It is hoped that the implementation of QR codes in this system can increase efficiency and convenience in the overall futsal field ordering process.